Guidelines for the use of antimicrobials based on the epidemiology of hospital microorganisms: the role of infection controllers - Marcelo Carneiro; Eliane Carlosso Krummenauer; Janete Aparecida Machado; Janine Rauber; Leandro Bizarro Muller (Universidade de Santa Cruz do Sul, 2012)
.